Witold Maisel, Archeologia prawna Europy, PWN, Warszawa—Poznań 1989 - Wąsowicz, Marek (Czasopismo Prawno-Historyczne, 1991)
Recenzja: Witold Maisel, Archeologia prawna Europy, PWN, Warszawa—Poznań 1989